APPROACHES TO ENHANCING REGIONAL ECONOMIES VIA INVESTMENT ATTRACTION THROUGH FREE ECONOMIC ZONES - Tollievna , Qarajanova Gulnoza (International Journal Multidisciplinary (IJMI), 2024)
This paper delves into the pivotal role of free economic zones (FEZ) in Uzbekistan, focusing on their potential to magnetize investment projects. It assesses the critical elements for successfully embedding FEZs within the regional economic framework, pinpointing prevalent challenges and hurdles. Emphasizing the need for robust legislative frameworks, the creation of a conducive investment climate, and the provision of essential infrastructure, the paper explores various investment project types and the dynamic roles of participants in the investment landscape. The goal is to elucidate strategies that can augment the efficacy of FEZs in bolstering investments and propelling regional economic progress in Uzbekistan.